ANALISIS WEBSITE QUALITY, TRUST DAN LOYALTY PELANGGAN ONLINE SHOP (STUDI KASUS MAHASISWA FAKULTAS EKONOMI DAN BISNIS TAHUN 2020) - Alfharobby, Wahyu (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research is titled "Analysis of Website Quality, Trust, and Customer Loyalty in Online Shops (case study of students of the Faculty of Economics and Business in 2020)." The purpose of this research is to determine the influence of Website Quality and Trust on Customer Loyalty (case study of students of the Faculty of Economics and Business in 2020). This study uses a quantitative data analysis research method. The population in this study consists of 139 students from the Faculty of Economics and Business in 2020. Data collection techniques involve interviews and observations. Based on the research results, multiple linear regression obtained the regression equation Y = 0.856 + 0.212X1 + 0.263X2, and the magnitude of the influence is evident from the coefficient of determination or R Square (R2) = 0.690, which is 69%, while the remaining 31% is influenced by other variables outside the study. Furthermore, Website Quality and Trust partially have a significant effect on Customer Loyalty with the probability values (sig) of each variable, namely Website Quality (X1) with probability (sig) 0.000 < alpha 0.05, having a t-value > t table for Website Quality (X1) (11.780 > 1.655), and the variable Trust (X2) with probability (sig) 0.001 < alpha 0.05, having a t-value > t table (10.691 > 1.655). Additionally, Website Quality and Trust simultaneously have a significant effect on Customer Loyalty with a probability (sig) of 0.001 < alpha 0.05, having an F-value > F table (151.029 > 3.68). Keywords: Website Quality, Trust, Customer Loyalty